Case report: A novel reciprocal ROS1-CD74 fusion in a NSCLC patient partially benefited from sequential tyrosine kinase inhibitors treatment - Zhang, Xugang; Wang, Baoming; Wang, Chunyang; Liao, Chengde; Wang, Shiping; Cao, Ran; Ma, Tonghui; Wang, Kun (Frontiers in Oncology, 2022)
Background: The clinical significance of majority oncogenic novel fusions are still unknown due to the scarcity. Reciprocal ROS1 translocation is a rare form of ROS1 fusion and have not yet been clearly analyzed. Case presentation: A 44-year-old Chinese woman with a large dimension in the left lobe of the lung was admitted to the hospital with IVB lung adenocarcinoma. It was discovered that the intron 28 of ROS1 and the intron 6 of CD74 produced an unique reciprocal ROS1 rearrangement. Additionally, the dual CD74-ROS1 fusions were discovered using the RNA-NGS findings. Though benefited from crizotinib and lorlatinib sequential treatment, the overall prognosis of the patient was relatively poor, whose progression-free survival (PFS) was 4 months for crizotinib treatment and 5 months for lorlatinib treatment, respectively. Conclusion: In summary, a novel ROS1-CD74 fusion identified by DNA-NGS was translated into dual CD74-ROS1 transcripts. Furthermore, this patient with non-small cell lung cancer benefited from consecutive TKI therapy. Our discovery broadened the range of targetable ROS1 fusions and underlined the importance of sequential DNA and RNA sequencing in identifying uncommon but beneficial fusions, which eventually bring benefits to the patients.